Not by Loyalty Alone - Gall, William R. (Academy of Management Journal, 1962)
Analyses the concept and challenge of loyalty in business organizations. Type of loyalty with which businessmen are concerned; Importance of loyalty in an organization; Conflict of loyalties in industries; Factors which affect the loyalty relationships in United States organizations; Meaning of integrity of purpose as criterion of loyalty in industry.